Negative Affectivity, Depression, and Resting Heart Rate Variability (HRV) as Possible Moderators of Endogenous Pain Modulation in Functional Somatic Syndromes - Van Den Houte, Maaike; Van Oudenhove, Lukas; Van Diest, Ilse; Bogaerts, Katleen; Persoons, Philippe; De Bie, Jozef; Van den Bergh, Omer (Frontiers in Psychology, 2018)
Abstract Background: Several studies have shown that patients with functional somatic syndromes have, on average, deficient endogenous pain modulation (EPM), as well as elevated levels of negative affectivity and high comorbidity with depression and reduced resting heart rate variability (HRV) compared to healthy controls. The goals of this study were 1) to replicate these findings and 2) to investigate the moderating role of negative affectivity, depression and resting HRV in EPM efficiency within a patient group with fibromyalgia and/or chronic fatigue syndrome. Resting HRV was quantified as the root mean square of successive differences between inter-beat intervals (RMSSD) in rest, a vagally-mediated time domain measure of HRV. Methods: Seventy-eight patients with fibromyalgia and/or chronic fatigue syndrome and 33 healthy controls completed a counter-irritation paradigm as a measure of EPM efficiency. Participants rated the painfulness of electrocutaneous stimuli (of individually calibrated intensity) on the ankle before (baseline phase), during (counter-irritation phase) and after (recovery phase) the application of a cold pain stimulus on the forearm. A larger reduction in pain in the counter-irritation phase compared to the baseline phase reflects a more efficient EPM. Results: In contrast to our expectations, there was no difference between pain ratings in the baseline compared to counter-irritation phase for both patients and healthy controls. Therefore, reliable conclusions on the moderating effect of negative affectivity, depression and RMSSD could not be made. Surprisingly, patients reported more pain in the recovery compared to the counter-irritation and baseline phase, while HC did not. This latter effect was more pronounced in patients with comorbid depression, patients who rated the painfulness of the counter-irritation stimulus as high and patients who rated the painfulness of the electrocutaneous stimuli as low. Conclusion: We did not manage to successfully replicate the counter-irritation effect in healthy controls or FSS patients. Therefore, no valid conclusions on the association between RMSSD, depression, negative affectivity and EPM efficiency can be drawn from this study. Possible reasons for the lack of the counter-irritation effect are discussed.